Comparison of 18F FDG PET-CT AND CECT in pretreatment staging of adults with Hodgkin's lymphoma. (January 2019) - Panebianco, Martina; Bagni, Oreste; Cenfra, Natalia; Mecarocci, Sergio; Ortu La Barbera, Elettra; Filippi, Luca; Codacci-Pisanelli, Giovanni; Biondi, Tommaso; Laghi, Andrea; Cimino, Giuseppe
Highlights: In HL staging, PET-CT is more sensitive than CECT. In localized HL, PET-CT may modify both prognostication and treatment. PET-CT was able to measure bulky disease similarly to CECT. PET-CT should replace CECT in the staging procedures of HL. Abstract: We compared 2-[fluorine-18] fluoro-2-deoxy-d -glucose PET-CT and contrast-enhanced computed tomography (CECT) in 62 consecutive patients with newly diagnosed Hodgkin Lymphoma (HL), aiming to provide evidences that may spare CECT from the staging procedures of HL patients. Among a total of 1448 nodal sites examined, disease involvement was detected in 232 (16%) and 280 (19.3%) nodal areas by CECT and PET-CT, respectively (P < 0.01). Sensitivity of CECT in detecting disease involvement ranged from 0% for internal mammary region (7 cases) and Waldayer's ring (1 case) to 100% for mediastinum. A total of 248 extranodal areas were examined. CECT and PET-CT identified disease involvement in 19 (7.7%) and 25 (10.1%) extranodal areas, respectively (P = n.s). Compared to PET-CT, CECT detected a lower number of cases with bone and/or bone marrow involvement (P = 0.05), whereas no differences were detected at the level of lung. By contrast, CECT identified liver lesions in four patients versus three identified by PET-CT. In comparison to CECT, PET-CT upstaged 6 patients (9.7%) and downstaged 1 patient (1.6%). We showed that PET-CT modified treatment strategy in five (8.1%) cases not only as a result of stage advancement (2 cases) but also of a different prognostic stratification in patients with localized disease (3 cases), due to the better sensitivity in detecting nodal involvement. In conclusion, our data, confirm the superiority of PET-CT in detecting disease involvement at diagnosis of HL, and further supports the possibility to replace CECT with PET-CT in the initial staging of HL.